Literature Review: The role and contribution of women fishermen in fishing households and the empowerment program - Lana Izzul Azkia; Muhammad Reza (Jurnal Perikanan Terpadu, 2026)
Capture fisheries serve as the primary source of income for coastal communities. However, the instability of fish catches often leads to economic vulnerability within fishing households. In this context, fisherwomen play a crucial role in supporting household economies through productive activities. This study aims to identify the roles and contributions of fisherwomen in fishing households and to describe empowerment programs that have been implemented. A literature review method was used, analyzing national scientific articles published between 2018 and 2024. The results showed that fisherwomen hold dual roles: in domestic responsibilities such as childcare, household management, and decision-making, and in economic activities such as fish processing, marketing, and small-scale enterprises. Empowerment programs—such as skills training, business mentoring, group enterprise development (KUBE), and digital marketing aim to enhance the economic capacity and independence of fisherwomen